Species groups of Crossodonthina Yosii (Collembola: Neanuridae), with the description of a new species and a new record for C. bidentata Luo & Chen - Jiang, Ji-Gang; Wang, Qing-Yun (Zootaxa, 2024)
A new two-eyed species of the genus Crossodonthina Yosii (Collembola: Neanuridae) is recorded and described from the Nanling National Forest Park, Ruyuan Yao Autonomous County, Guangdong Province, China. Crossodonthina quadridentata sp. nov. is characterized by 2+2 eyes, labral chaetotaxy formula as 4/4, 2, cephalic chaeta O present, cephalic tubercles Dl, L and So fused together, mandible with 4 basal teeth and 5 fringed rami, and maxilla with two lamellae, the outer lamella apically bifurcated, the inner lamella ciliated. Crossodonthina bidentata Luo & Chen is also recorded for the first time in the Mount Wuyi National Nature Reserve, Fujian Province. The genus Crossodonthina is herein tentatively divided into two species groups. The main differences between the montana and the nipponica groups are listed and discussed, and the importance of the number of eyes in the classification of Neanuridae is stressed.